SUSTAINABLE FARMS: INTEGRATION OF AGRICULTURAL SYSTEMS - Manolo Muñoz-Espinosa; Jorge Artieda-Rojas; Santiago Espinosa-Vaca; Segundo Curay-Quispe; Marco Pérez-Salinas; Oscar Nuñez-Torres; Rafael Mera-Andrade; Hernán Zurita-Vásquez; Giovanny Valátegui-Espin; Pedro Pomboza-Tamaquiza; Anselmo Carrasco-Silva; Marcos Antonio Barros-Rodriguez (Tropical and Subtropical Agroecosystems, 2016)
The inappropriate use of agrochemicals and technologies in farming systems can cause an accelerated deterioration of agricultural and soil pollution. Thus, agriculture and livestock are becoming an environmental problem in the world, which implies the need to assess the efficiency of agricultural production systems related to sustainability. The traditional peasant system is apparently unsustainable, while farm with an integral production approach have better opportunities for development over time as they tend to sustainability. This type of farms incorporate productive alternatives that improve as a whole, the system and the livelihood of the peasants. The trends towards sustainability of farms are mainly due to a better land use. As well as, implementing systems adapted to each soil and production type to ensure profitability and persistence, achieving the highest possible agricultural productivity. The urgency to produce food for a growing population is almost a paradigm that reinforces the imperative for maximum yield per unit area, and creates a vision of the rural world aimed at increasing profit at the expense of the attributes and core values of livelihood in rural areas. It can be concluded that the integrated farming articulate various subsystems, which working together could allow higher sustainability of agricultural production practices, environmentally friendly, safeguarding the food sovereignty of the population and improving the quality of life of farmers